ANALISIS PROBLEMATIKA SUSUNAN KALIMAT BAHASA ARAB BAGI MAHASISWA SAINS DAN TEKNOLOGI - Nikmah, Unzilatun; Khikmah, Mambaul Maysyatil; Mustofa, Saiful (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2024)
The purpose of this study was to determine the problems of Arabic sentence construction and its solutions for students of the Faculty of Science and Technology in the first semester of 2023 Maulana Malik Ibrahim State Islamic University Malang from the aspect of sentence structure (tarkib) during the learning of a special program for Arabic language development (PKPBA). This research method uses a qualitative-descriptive approach with case studies. The object of this research is first semester students in 2023, with a sample of 40 students. The data collection techniques used were observation and interview. Data analysis was carried out through three stages, data reduction, data presentation, and conclusions. Triangulation used to test the validity of the data is triangulation of sources and methods. The results showed that the problems of Arabic sentence structure are difficulties in arranging changes in the end of the sentence (i'rab), determining the order of words in the sentence, and determining the suitability of words in the sentence. The solutions include: studying Arabic grammar rules in depth, practicing making words in sentences continuously, and often reading Arabic texts carefully.